Effective Strategies For Quality Cost Management In The Concrete Industry During The Pandemic - A'yunin, Eka Qurratu; Adam, Helmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study addresses the urgency of achieving quality-cost efficiency in the concrete industry amid the COVID-19 pandemic. The primary objectives are to identify quality cost components, analyze their management during the pandemic, and propose measures to enhance efficiency. This qualitative descriptive study employs a case study approach using primary data on quality costs from CV. Maju Djaya Beton for the years 2019 to 2021. The analysis involves identifying relevant cost components, preparing quality cost reports based on actual sales, and evaluating trends. The results reveal that the pandemic did not significantly affect the company's quality-cost management. In 2020, quality cost burdens increased compared to 2019, but in 2021, all cost components—prevention, appraisal, internal failure, and external failure—decreased. The company optimized its quality cost budget by focusing on quality engineering and rework, thereby improving product quality. The findings highlight the importance of effective cost-allocation strategies to minimize losses and enhance efficiency, especially during a pandemic. These insights provide valuable guidance for the concrete industry to maintain product quality while achieving cost efficiency during crises.